2014
DOI: 10.1007/s11340-013-9829-z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Perforation Process of 5754-H111 and 6082-T6 Aluminium Plates Subjected to Normal Impact by Conical, Hemispherical and Blunt Projectiles

Abstract: This paper presents an experimental investigation on the perforation behaviour of 5754-H111 and 6082-T6 aluminium alloys. The mechanical response of these materials has been characterized in compression with strain rates in the range of 10 −3 s −1 <ε < 5 • 10 3 s −1 . Moreover, penetration tests have been conducted on 5754-H111 and 6082-T6 plates of 4 mm thickness using conical, hemispherical and blunt projectiles. The perforation experiments covered impact velocities in the range of 50 m/s < V 0 < 200 m/s. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 54 publications
7
27
1
1
Order By: Relevance
“…Low-rate compression Figure 1a shows the representative quasi-static compression stress-strain curves for Haynes 282. The rate sensitivity is negligible within this range of strain rates, which is a common characteristic of other metallic alloys [21]. Figure 1b compares the quasi-static behavior of Inconel 718, obtained from literature, and the experimental results in the present work for Haynes 282.…”
Section: Quasi-static Compression Testingsupporting
confidence: 61%
“…Low-rate compression Figure 1a shows the representative quasi-static compression stress-strain curves for Haynes 282. The rate sensitivity is negligible within this range of strain rates, which is a common characteristic of other metallic alloys [21]. Figure 1b compares the quasi-static behavior of Inconel 718, obtained from literature, and the experimental results in the present work for Haynes 282.…”
Section: Quasi-static Compression Testingsupporting
confidence: 61%
“…However, for the aluminum alloys studied, higher differences of Lode parameter and stress triaxiality are found in moderate/high hardening materials. From experimental studies [20,21], the following features of the alloys used in this work can be stated: AA 5754-H111 has low strength/moderate hardening, AA 6082-T6 has moderate strength/low hardening, and AA 2024-T351 has the high strength/high hardening. Barsoum et al [10] concluded that the sensitivity to the Lode parameter increases with higher material yield strength accompanied with a decrease in hardening.…”
Section: Resultsmentioning
confidence: 96%
“…The second alloy shows largely different mechanical response with high initial yield stress, low strain hardening, and limited ductility. The third of them shows greater ductility and greater initial yield stress [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heating rate and cooling rate are also critical parameters for the HFQ® process and should be controlled accurately to maintain a supersaturated solid solution without grain degradation in a specimen. Aluminium alloy 6082-T6, which is extensively used in the automotive industry [31], was used as the sample material to carry out the investigation. The specimen was heated to the solution heat treatment temperature 535°C [32] at a heating rate of 30°C/s, soaked for 1 min and then cooled to a designated temperature in the range of 370-510°C at a cooling rate of 100°C/s [2].…”
Section: The Principles Of the Experimental Designmentioning
confidence: 99%